ABNORMAL AND TRANSIENT MODES OF THE CONVERTER BOOSTER TYPE FOR DC TRACTION SUBSTATIONS - Goncharov, Yu. P.; Zamaruev, V. V.; Ivahno, V. V.; Panasenko, N. V.; Bozhko, V. V.; Andryenko, P. D.; Lahuta, I. I. (Science and Transport Progress, 2009)
The results of analytical research and computer design of the anomalous, steady-state and transitional modes related to the resonance in the input filter of voltage added converter based on IGBT with the PWM are presented. The ways of resonance removal by both the control means and the power blocks, combined with the overvoltage protection, are offered.